Scattering of electromagnetic wave by linear chain of charged particles - Ognivenko, V.V. (Вопросы атомной науки и техники, 2002)
The Thomson scattering of a plane monochromatic electromagnetic wave by a linear chain of periodically spaced charged particles is investigated theoretically. It is obtained a functional dependence for the total power and angular distribution of this radiation as a function of the number of the charged particles and the distance between them. The coherence effects for a linear chain of pointlike bunches are discussed.